Efficacy and Safety of Insulin Glargine 300 U/mL in People with Type 2 Diabetes Uncontrolled on Basal Insulin: The 26-Week Interventional, Single-Arm ARTEMIS-DM Study - Sethi, Bipin (2022)
Introduction: The efficacy and safety of switching to insulin glargine 300 U/mL (Gla-300) in type 2 diabetes mellitus (T2DM) uncontrolled on basal insulin (BI) has been demonstrated in the North American and Western European populations; however, there is limited data from other geographical regions with different ethnicities. The ARTEMIS-DM study aimed to evaluate the efficacy and safety of Gla-300 in people with T2DM uncontrolled on BI from Asia, Latin America and Middle East Africa. Methods: The ARTEMIS-DM was a 26-week, prospective, interventional, single-arm, phase IV study (NCT03760991). Adults with T2DM previously uncontrolled (glycated haemoglobin [HbA1c] 7.5–10%) on BI were switched to Gla-300. The primary endpoint was change in HbA1c from baseline to 26 weeks. Key secondary endpoints were changes in HbA1c (week 12), fasting plasma glucose (FPG), self-monitored plasma glucose (SMPG) and BI dose from baseline to week 26. The safety and tolerability of Gla-300 were also assessed. Results: A total of 372 (50% male) participants were included, with mean (standard deviation [SD]) age 60.9 (10.0) years, duration of diabetes 13.11 (7.48) years and baseline HbA1c 8.67 (0.77)% (71.22 [8.44] mmol/mol). A total of 222 (59.7%) participants were using insulin glargine 100 U/mL and 107 (28.8%) were using neutral protamine Hagedorn insulin as previous BI. There were clinically significant reductions in mean HbA1c (− 0.82%; primary endpoint), FPG and SMPG levels at week 26. With a pre-defined titration algorithm, mean Gla-300 dose increased from 27.48 U (0.35 U/kg) at baseline to 39.01 U (0.50 U/kg) at week 26. Hypoglycaemia events occurred in 20.4% of the participants; 1 (0.3%) participant had a severe hypoglycaemia event. Conclusion: In people with T2DM uncontrolled on previous BI, switching to Gla-300 with optimal titration guided by an algorithm was associated with improved glycaemic control and low incidence of hypoglycaemia across multiple geographic regions. ClinicalTrials.gov identifier: NCT03760991.